Analisis Pendapatan dan Kelayakan Usaha Minyak Nilam di Kecamatan Kluet Tengah Kabupaten Aceh Selatan - Jumadi Ahmad; Firdaus Firdaus; Syarifuddin Syarifuddin (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Patchouli plant is a plant that produces patchouli oil. Patchouli oil refinery is a potential business to be developed because Indonesia has a tropical climate that is suitable for planting patchouli plants. And businesses that can utilize local resources and are oriented towards the export market. The purpose of this study was to determine the amount of income derived from the patchouli oil business and to analyze the feasibility of the patchouli oil business in Kluet Tengah District, South Aceh Regency. The research method used survey method. The sampling technique is